2011
DOI: 10.1016/j.cell.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Double-Strand Breaks in Heterochromatin Move Outside of a Dynamic HP1a Domain to Complete Recombinational Repair

Abstract: SUMMARY Double-strand breaks (DSBs) in heterochromatic repetitive DNAs pose significant threats to genome integrity, but information about how such lesions are processed and repaired is sparse. We observe dramatic expansion and dynamic protrusions of the heterochromatin domain in response to ionizing radiation (IR) in Drosophila cells. We also find that heterochromatic DSBs are repaired by homologous recombination (HR) but with striking differences from euchromatin. Proteins involved in early HR events (resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
885
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(964 citation statements)
references
References 61 publications
47
885
1
2
Order By: Relevance
“…17 In contrast, knockdown of the HP1 Drosophila ortholog HP1a does not impair RAD51 recruitment. 18 Intriguingly as well, knocking-out of C. elegans HP1 orthologs (hpl-1 and hpl-2) leads to opposite outcomes on cell survival after ionizing radiation (IR): hpl-1 KO shows increased resistance to IR, while hpl-2 KO is highly sensitive. 14 Therefore, it is necessary to sort out the particular contribution of each HP1 paralog in the DDR and the molecular mechanisms at stake.…”
Section: Introductionmentioning
confidence: 99%
“…17 In contrast, knockdown of the HP1 Drosophila ortholog HP1a does not impair RAD51 recruitment. 18 Intriguingly as well, knocking-out of C. elegans HP1 orthologs (hpl-1 and hpl-2) leads to opposite outcomes on cell survival after ionizing radiation (IR): hpl-1 KO shows increased resistance to IR, while hpl-2 KO is highly sensitive. 14 Therefore, it is necessary to sort out the particular contribution of each HP1 paralog in the DDR and the molecular mechanisms at stake.…”
Section: Introductionmentioning
confidence: 99%
“…It appears unlikely that HR can occur on such highly condensed substrates. However, the discovery the HR may be the predominant DSB-repair pathway for heterochromatic DSBs (Goodarzi et al 2010;Chiolo et al 2011) suggests that specific mechanisms may exist for HR to act on highly condensed substrates. Although chromosome condensation may provide an intuitive barrier to HR, in turn, HR has been shown to affect chromosome condensation.…”
Section: Regulation and Coordination With Nuclear Structure And Functionmentioning
confidence: 99%
“…First, centromeres do participate in HR but centromeric HR is specifically restricted to gene conversion (Shi et al 2010). Second, it was shown that DSB repair in heterochromatic regions was specifically channeled to HR-mediated repair (Chiolo et al 2011). This seminal counterintuitive finding discovered that the broken chromosome (and presumably its unbroken sister chromatid template) is extruded from the heterochromatic subcompartment to insulate the repair process from other repeat templates to avoid genomic rearrangements.…”
Section: Centromere Function and Recombination In Heterochromatinmentioning
confidence: 99%
“…DSBs within rDNA repeats were found to transiently exit the Rad52/recombination-repressive environment of the nucleolus in which they typically reside to undergo repair without compromising genome integrity 8,9 . In flies, heterochromatic DSBs exit their Rad51/recombinationrepressive subnuclear domain to undergo repair 10 . Similarly, heterochromatic DSBs were found to relocate outside their domain for repair in cultured human cells 11 .…”
mentioning
confidence: 99%